Adenocarcinoma arising in an ectopic enterogenous cyst: A rare case report and review of literature - Du, Haina; Xu, Dachao; Zhang, Shuhui; Zhang, Xinliang; Fang, Mingzhi; Li, Min (Frontiers in Oncology, 2022)
Enterogenous cyst (EC) is a rare congenital lesion generally located in the central nervous system, such as in the cerebral hemispheres, posterior fossa, or spinal canal. They are usually benign lesions, and malignant transformation is rare. A 42-year-old woman felt obvious pain in the lump and went to a local hospital for local lumpectomy. After 7 months, she again felt pain in the buttocks and difficulty in urinating and defecation. The computed tomography (CT) scan showed a mass in the pelvis. Sacrococcygeal cyst excision was performed 10 days later, and postoperative pathology showed epidermoid cyst. Shortly after the patient recovered and was discharged from the hospital, the pain in the buttocks continued to recur. A total of 5 times of puncture and drainage were performed. Later, the patient went to our hospital for treatment, and pelvic MRI showed multiple abnormal signal shadows in the presacral and sacrococcygeal regions, some of which were considered abscesses, and some were cystic lesions. She underwent tumor resection and was diagnosed with EC with locally moderately differentiated adenocarcinoma. 4 months later, the patient's symptoms of swelling and pain recurred. MRI examination showed multiple high-signal T2 shadows in the anterior sacral and subcutaneous tissues of the buttocks, and enhanced scan showed partial marginal enhancement. After assessment, the patient was given a radiation dose of 60Gy/25F. ECs in the anterior sacral and soft tissue of the buttocks are very rare, and the case of carcinomatous transformation has never been reported. Therefore, we discussed the clinicopathological features of ectopic enterogenous cysts and reviewed the literature.